Histopathological changes in the perivisceral fat body of Rhinocricus padbergi (Diplopoda, Spirobolida) triggered by biosolids - Francisco, Annelise [UNESP]; Christofoletti, Cintya Aparecida; Neto, Nilton Righetto [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Springer, 2015)
Human activities generate a great amount of sewage daily, which is dumped into the sewer system. After sewage-treatment processes, sewage sludge is generated. Such byproduct can be treated by different methods; the result of treatment is a stabilized compost of reduced pathogenicity that has a similar inorganic chemical composition to the raw sewage sludge. After such pretreatment, sewage sludge is called a biosolids, and it can be used in agriculture. In this contest, the present study evaluated the effects of a sample of biosolids on the perivisceral fat body of a diplopod. These invertebrates are soil organisms that play an important role in the dynamics of terrestrial ecosystems, and as a consequence, they are in contact with xenobiotics present in this environmental compartment. Special emphasis is given on the interpretation of the effects of complex mixtures in target organs of diplopods. A semiquantitative analysis for the evaluation of histopathological changes in the perivisceral fat body was proposed. The sample-induced histopathological and ultrastructural changes in individuals exposed to it, and the severity of the effects was positively related to the exposure time, resulting in the deaths of exposed individuals after 90 days. Thus, the results indicate the need for caution in the use of biosolids as well as the need for improving waste management techniques, so they will produce environmentally innocuous final products.
Keywords: Electron microscopy; Histopathology; Millipede; Oenocyte; Sewage sludge; Spherocrystals